Risk Area: The firefly narration - Pol Colmenares , Ana (Re-visiones, 2024)
This article draws a line between the experience of shock in modernity as described by Benjamin, and the current state of overstimulation that collapses our perceptual system. It includes the recent analysis by Crary about a society whose objective is to stay active twenty-four hours a day, consuming and producing. To address these issues, we stress the need to incorporate an emotional approach, briefly reviewing the concepts of vulnerability and risk. We also address the absence of narration and experiential content, and their transformation into other information-based models. Finally, we consider an episode of Black Mirror that deals with relations between new technologies, affects and acts of creation/resistance in our society.